Kelimpahan Larva Ikan Pada Kondisi Air Pasang Dan Surut Di Muara Sungai Pilang Sari, Desa Pidodo Kulon, Kendal [Abundance Of Fish Larvae In Neap And Tide Condition In Estuary Of Pilang Sari River, Pidodo Kulon Village, Kendal ] - Abdul Manan (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract The aim of this research is to know the abundance of fish larvae in neap and tide condition in estuary of Pilang Sari river, Pidodo Kulon village, Kendal. This research is case study where the fish larvae that been caught was deeply observed in the limited time, place and population. Sample was taken in the three place. Data were collected used seine net when the neap and tide of sea level. The number of fish larva that been caught during the research are 12.983. Including from 8 genus are Stolephorus, Ambassis, Periapthalmus, Gerres, Leiognathus, Terapon, Atherinomarus. The composition of fish larvae that been caught when neap and tide was dominated by Stolephorus and Ambassis. When the new moon phase, the number of fish larvae that been caught is 1151, quarter moon is 2379, full moon is 5243 and three–quarters of the moon is 4110 fish larvae. The result of this research shows the relationship between the pattern of tide and amount of the fish larvae that been caught every moon phase. In the sping tide pattern, amount of the fish larvae that been caught was bigger than neap tide pattern. In commonly, fish larvae that been caught when the tide is bigger than abundance of fish larva that caught when the water was neap.